2015
DOI: 10.1038/cddis.2015.136
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate opposes HBV-induced incomplete autophagy by enhancing lysosomal acidification, which is unfavorable for HBV replication

Abstract: Epigallocatechin-3-gallate (EGCG), a major polyphenol in green tea, exhibits diverse beneficial properties, including antiviral activity. Autophagy is a cellular process that is involved in the degradation of long-lived proteins and damaged organelles. Recent evidence indicates that modulation of autophagy is a potential therapeutic strategy for various viral diseases. In the present study, we investigated the effect of EGCG on hepatitis B virus (HBV) replication and the possible involvement of autophagy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 51 publications
1
70
1
Order By: Relevance
“…Evidence indicates that HBx plays a crucial role in HBV-induced autophagosome formation, which is required for HBV replication (28)(29)(30)(31)(32). As our data revealed that HBx induces autophagy via the ROS-JNK signaling pathway, we further examined the role of this signaling pathway in HBV-induced autophagy and its replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence indicates that HBx plays a crucial role in HBV-induced autophagosome formation, which is required for HBV replication (28)(29)(30)(31)(32). As our data revealed that HBx induces autophagy via the ROS-JNK signaling pathway, we further examined the role of this signaling pathway in HBV-induced autophagy and its replication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that autophagy is an important host factor in the regulation of the replication of diverse viruses, such as dengue virus, poliovirus, influenza virus A, and coxsackievirus B3 virus, as well as HBV (25)(26)(27)(28)(29)(30)(31)(32). Evidence indicates that HBV can activate autophagosome formation, which is required for its own replication (28)(29)(30)(31)(32). Furthermore, HBx appears to play an important role in HBV-induced autophagosome formation (28,(33)(34)(35)(36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For HBV, Sir D et al first reported that HBV could activate the early autophagic pathway (7). But it seems like autophagy causes no harm to HBV (8). The precise underlying mechanisms why the enhanced autophagosomes promote HBV DNA replication instead of engulfing it need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolyzable tannins are known to be hydrolyzed into smaller polyphenols, such as gallic or ellagic acids, it is therefore conceivable that the inhibition of cccDNA formation and stability by tannin is attributed to different hydrolysis products and/or other metabolites. Gallic or ellagic acids have been shown to inhibit multiple steps in HBV life cycle, including virus entry (Huang et al, 2014), DNA replication (He et al, 2011; Zhong et al, 2015), and HBeAg secretion (Shin et al, 2005). However, the direct effect of hydrolyzable tannins on cccDNA metabolism has not been studied.…”
Section: Discussionmentioning
confidence: 99%